Detection of Methicillin-Resistance Gene (mec-A) in Staphylococcus aureus Strains by PCR and Determination of Antibiotic Sensitivity - Alireza Zamani (پزشکی بالینی ابن سینا, 2007)
Background & Objective: Methicillin–Resistant Staphylococcus aureus (MRSA) is one of the most important causes of hospital infections worldwide. Treatment of these infections has become more difficult because of resistance to methicillin/oxacillin and other antibiotics. The aim of this study was to determine the incidence of MRSA infections in hospitals affiliated to Hamadan University of Medical Sciences.